Epoxy glue composition and camera assembly bonded by using same
By using acidic polyester copolymer and high molecular weight copolymer silyl ammonium salt as additives in the epoxy glue composition, the problem of unstable viscosity of epoxy glue is solved, and the viscosity stability and bond strength of epoxy glue is improved, meeting the high reliability needs of the vehicle-mounted ADAS camera.
Patent Information
- Application Number
- CN202510097118.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-15
AI Technical Summary
The viscosity of existing epoxy glues is unstable during the dispensing process, resulting in unstable process and poor quality of finished products, which cannot meet the high reliability needs of the on-board ADAS camera.
By using a copolymer containing acidic polyester and a high molecular weight copolymer silyl ammonium salt as an auxiliary agent in the epoxy glue composition, the free ions released by the heat curing agent are captured and the composition is balanced, thereby stabilizing the viscosity and improving the bonding strength.
The viscosity stability and bond strength of epoxy glue are improved, ensuring the reliability of the dispensing process and the high reliability of the finished product, and meeting the high stability needs of the on-board ADAS camera.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy adhesives, and in particular to an epoxy adhesive composition and a camera assembly bonded therewith. Background Art
[0002] The lens and base materials of vehicle-mounted ADAS cameras are usually made of anodized aluminum, PPS, PBT, etc., and the components are generally assembled together by gluing. For the safe use of the car, the reliability requirements of the vehicle-mounted ADAS camera are high. In order to achieve high reliability, the glue of the camera needs to have a high bonding strength to complete the reliability of the bonding. However, in the related technology, the viscosity of the glue is often unstable and changes dynamically during the dispensing process, which in turn affects the overall process, such as affecting the predetermined glue output and causing unstable process quality. In addition, the unstable viscosity will also affect the wetting effect of the produced glue, affecting the final use effect.
[0003] In view of this, it is necessary to improve the composition of epoxy glue to make its viscosity more stable and better meet the high stability requirements of on-board ADAS cameras. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is to provide an epoxy adhesive composition and a camera assembly bonded therewith.
[0005] In the related art, epoxy glue often has the problem of unstable viscosity and frequent dynamic changes during the dispensing process. The inventors of the present application have found through a lot of creative research that the fundamental reason is that the thermosetting agent used in the epoxy glue will slowly release cations, and the released cations will trigger reactions between the substances in the epoxy glue, thereby causing the viscosity of the glue to change, resulting in unstable process and poor quality stability of the finished product.
[0006] In order to solve this problem, the first aspect of the present invention provides an epoxy adhesive composition, comprising the following components in parts by weight:
[0007] Epoxy resin 5-20 parts, toughening agent 2-10 parts, epoxy diluent 2-10 parts, light curing agent 0.1-1 parts, heat curing agent 0.1-1 parts, filler 40-80 parts, coupling agent 0.1-1 parts, thixotropic agent 5-10 parts, auxiliary agent 0.1-2 parts;
[0008] The auxiliary agent includes one or more of a copolymer containing acidic polyester and a high molecular weight copolymer silane ammonium salt.
[0009] The present application uses one or more of copolymers containing acidic polyesters and high molecular weight copolymer silane ammonium salts as auxiliary agents in the formula, and uses the acidity and alkalinity of the above substances to capture the free ions released by the thermal curing agent, balancing the composition, making the viscosity of the epoxy adhesive stable, and the process reliable during the dispensing process, ensuring the bonding strength and high reliability of the product after bonding. Not only that, the auxiliary agent of the present application also has a better dispersion effect on powders, especially fillers, avoiding the problems of stress breakthrough points caused by voids caused by filler agglomeration, and further improving the reliability of the product.
[0010] In a possible implementation of the present application, the acid value of the copolymer containing the acidic polyester is in the range of 30 to 150 mg KOH / g; and the amine value of the molecular weight copolymer silyl ammonium salt is in the range of 20 to 60 mg KOH / g.
[0011] Through creative research, the present application has found that controlling the acid value and the amine value within the above range will achieve the best effect. If the amine value and the acid value are too high, the reaction will be affected and the reaction speed will be slowed down. If the amine value and the acid value are too low, the amount of additives added will increase, which will bring about side effects such as introducing too many small molecules to affect the interface, and will also have an adverse effect on the overall effect.
[0012] In a possible implementation of the present application, the copolymer containing the acidic polyester includes a copolymer containing a phosphoric acid polyester.
[0013] As an optional method, the copolymer containing acidic polyester may be BYK-W9010 (I1) (copolymer containing phosphoric acid polyester) or ANTI-TERRA-U100 (I3) (salt containing unsaturated polyamine amide and low molecular weight acidic polyester). The high molecular weight copolymer silane ammonium salt may be BYK-9076 (I2).
[0014] In a possible implementation of the present application, the epoxy resin includes one or more of alicyclic epoxy resin and hydrogenated bisphenol A epoxy resin (A3).
[0015] In a possible implementation of the present application, the alicyclic epoxy resin includes one or more of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (A1) and bis((3,4-epoxycyclohexyl)methyl)adipate) (A2).
[0016]
[0017] In a possible implementation of the present application, the toughening agent includes a core-shell toughening agent, and the core-shell toughening agent includes one or more of a mixture of core-shell styrene butadiene rubber and epoxy resin, a mixture of core-shell butadiene rubber and epoxy resin, and a mixture of core-shell polybutadiene rubber and epoxy resin. For example, Kaneka Japan MX series toughening agents MX125, MX553, MX279, etc. can be used.
[0018] In a possible implementation of the present application, the epoxy diluent is an oxetane-type active diluent, and the oxetane-type active diluent includes one or more of 3-ethyl-3-oxetane methanol (D1), 3,3'-(oxybismethylene)bis(3-ethyl)oxetane (D2), and 4,4-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl (D3).
[0019]
[0020]
[0021] In a possible implementation of the present application, the photocuring agent includes diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate (EA1) (such as CPI-100P produced by San Apro Co., Ltd.), one or more mixed triarylsulfonium hexafluorophosphates (EA2) (such as UVI-6990 produced by Union Carbide Corporation).
[0022] In a possible implementation of the present application, the thermal curing agent includes one or more of a thermal cationic polymerization initiator (EB1) of a salt composed of hexafluoroantimonate anions and cations (such as SI-80L produced by Sanshin Chemical Industry Co., Ltd.), and a thermal cationic polymerization initiator (EB2) of a salt composed of tetrakis(pentafluorophenyl)borate anions and cations (such as CXC-1821 produced by King Industries).
[0023] In a possible implementation of the present application, the filler may be at least one of SC6200-SPD (F1) and FA920G-SQ (F2) of the Admatechs silica powder series.
[0024] The surface sphericity, treatment degree and powder particle size matching of this series of fillers enable the powder to reinforce the glue, improve the strength of the glue and reduce the shrinkage rate and expansion coefficient of the glue.
[0025] In a possible implementation of the present application, the coupling agent may use at least one of Dow Corning's Z-6040 (G1) (glycidoxypropyltrimethoxysilane) and 3-glycidyloxypropyltrimethoxysilane (KBM-403E manufactured by Shin-Etsu Chemical Co., Ltd.) (G2).
[0026] In a possible implementation of the present application, the thixotropic agent (H) is fumed silica (such as R202 from Evonik).
[0027] In a possible implementation of the present application, the epoxy adhesive composition includes the following components in parts by mass: 3 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 3 parts of bis((3,4-epoxycyclohexyl)methyl)adipate), 3 parts of hydrogenated bisphenol A epoxy resin, 3 parts of core-shell structure toughener, 5 parts of 3-ethyl-3-oxetane methanol, 1 part of diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, 1 part of thermal cationic polymerization initiator of a salt composed of tetrakis(pentafluorophenyl)borate anions and cations, 60 parts of silicon powder, 0.5 parts of glycidoxypropyltrimethoxysilane, 7 parts of fumed silica, and 0.1 parts of a copolymer containing phosphate polyester.
[0028] The second invention, the present application provides a camera assembly, which is made by bonding the components of the assembly using an epoxy adhesive composition as described in any one of the first aspects.
[0029] The present invention optimizes the components of epoxy glue, uses one or more of a copolymer containing acidic polyester and a high molecular weight copolymer silyl ammonium salt as an auxiliary agent, utilizes the acidity and alkalinity of the above substances to capture free ions released by a thermal curing agent, and balances the composition, so that the viscosity of the prepared epoxy glue is stable, the process is reliable during the dispensing process, and the bonding strength and high reliability of the bonding rear camera, especially the vehicle-mounted ADAS camera, are guaranteed. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the specific embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
[0031] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0033] This embodiment provides an epoxy adhesive composition, comprising the following components in parts by weight:
[0034] Epoxy resin 5-20 parts, toughening agent 2-10 parts, epoxy diluent 2-10 parts, light curing agent 0.1-1 parts, heat curing agent 0.1-1 parts, filler 40-80 parts, coupling agent 0.1-1 parts, thixotropic agent 5-10 parts, auxiliary agent 0.1-2 parts;
[0035] The auxiliary agent includes one or more of a copolymer containing acidic polyester and a high molecular weight copolymer silane ammonium salt.
[0036] In this embodiment, the copolymer containing acidic polyester uses BYK-W 9010 (I1) (copolymer containing phosphoric acid polyester) or ANTI-TERRA-U100 (I3) (salt containing unsaturated polyamine amide and low molecular weight acidic polyester). The above-mentioned high molecular weight copolymer silyl ammonium salt uses BYK-9076 (I2). Comparative Example 5 uses BYK-P 104 (I4) (solution containing low molecular weight unsaturated polycarboxylic acid polymer).
[0037] The acid values or amine values of the above substances are as follows:
[0038] Acid value Amine value BYK-W 9010 129mg KOH / g ANTI-TERRA-U100 50mg KOH / g BYK-9076 38mg KOH / g 44mg KOH / g BYK-P 104 180mg KOH / g
[0039] The epoxy resin may be one or more of alicyclic epoxy resin and hydrogenated bisphenol A epoxy resin (A3). The alicyclic epoxy resin includes one or more of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (A1) and bis((3,4-epoxycyclohexyl)methyl)adipate (A2).
[0040]
[0041]
[0042] The toughening agent includes a core-shell toughening agent, and the core-shell toughening agent includes one or more of a mixture of core-shell styrene butadiene rubber and epoxy resin, a mixture of core-shell butadiene rubber and epoxy resin, and a mixture of core-shell polybutadiene rubber and epoxy resin. The embodiment of the present application uses Kaneka Japan MX series toughening agent MX125.
[0043] The epoxy diluent is an oxetane-based active diluent. In this embodiment, one or more of 3-ethyl-3-oxetanemethanol (D1) and 4,4-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl (D3) are used.
[0044]
[0045] The photocuring agent in this embodiment uses diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate (EA1) (CPI-100P manufactured by San Apro Co., Ltd.) and the thermal curing agent uses a thermal cationic polymerization initiator (EB2) composed of tetrakis(pentafluorophenyl)borate anions and cations (CXC-1821 manufactured by King Industries).
[0046] The fillers used were SC6200-SPD (F1) and FA920G-SQ (F2) of the silicon micropowder series of Admatechs. In Comparative Example 4, NQ-1120D (F3) of the silicon micropowder series of Lianrui New Materials was used.
[0047] The coupling agent used was Dow Corning's Z-6040 (G1).
[0048] The thixotropic agent (H) is fumed silica (such as R202 from Evonik).
[0049] Based on the above content, the following experiments of Examples 1-4 and Comparative Examples 1-5 were set up, as shown in the following table:
[0050] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Resin A1 6 3 6 6 6 6 6 6 Resin A2 3 6 Resin A3 3 3 3 3 3 3 3 3 3 Toughener B1 3 3 3 3 3 3 3 3 3 Epoxy Thinner D1 5 5 5 5 5 5 5 5 Epoxy Thinner D3 5 Light curing agent EA1 1 1 1 1 1 1 1 1 1 Thermal curing agent EB2 1 1 1 1 1 1 1 1 1 Filling F1 30 30 30 30 30 30 30 30 Filler F2 30 30 30 30 30 30 30 30 Filler F3 60 Coupling agent G1 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Thixotropic Agent H 7 7 7 7 7 7 7 7 7 Additive I1 0.1 0.1 0.3 0.1 0.1 0.1 Additive I3 0.1 1 Additive I4 0.1 1 0.1
[0051] The bonding effect verification tests of Examples 1-4 and Comparative Examples 1-5 were conducted respectively:
[0052] Among them, viscosity is tested using Brook field CAP2000+;
[0053] Among them, CTE1 and CTE2 are the expansion coefficient below the glass transition temperature and the expansion coefficient above the glass transition temperature, respectively, and are tested using TMA equipment;
[0054] Among them, the bonding strength is tested using the die shear equipment Dage 4000, and the maximum shear force that pushes the camera off is the bonding strength;
[0055] The double 85 aging test refers to placing the camera in a high temperature and high humidity box at 85°C and 85% humidity for 1000 hours, then taking the camera out and cooling it for two hours before testing the bonding strength.
[0056] Among them, the -40℃~120℃ temperature shock test means placing the camera in a hot and cold shock box, storing it at -40℃ for 30 minutes, transferring it to a 120℃ hot environment box within 30 seconds, and testing the bonding strength after 1000 cycles.
[0057] The specific test results are as follows:
[0058]
[0059] From the comparison of the data in the table, we can see that:
[0060] A. From the comparison between Comparative Example 1 and Example 1, it can be seen that without adding the additive of the present application (copolymer containing acidic polyester), the viscosity of the glue of Comparative Example 1 increased by more than 30% after three days at room temperature, and the strength of the glue decreased. The stability and viscosity of the glue were significantly worse than those of Example 1 to which the additive of the present application was added;
[0061] B. Comparison between Example 2 and Example 1 shows that in Example 2 using three resins, the glue toughness is increased, the bonding strength is improved, and the effect is better;
[0062] C. Comparing Example 3 with Example 1, the amount of additive added in Example 3 is increased. The experimental results show that the stability of Example 3 does not change for 7 days, but the bonding strength decreases, mainly because the additive is used too much, so that the small molecules affect the interface strength;
[0063] D. Example 4 is compared with Example 1. The results show that the stability does not change after 7 days of using the I3 additive, but the bonding strength of the glue with a curing time of 80°C*60min is reduced, because amines will neutralize some cationic initiators, thereby reducing the performance of the glue with a curing temperature of 80°C;
[0064] E. Comparison between Example 2 and Example 4 shows that the amount of additive I3 used is significantly increased, but the results show that the mechanics of the glue at 80°C*60min is very small, indicating that excessive addition of additives will cause the glue to be too stable, thereby affecting the performance;
[0065] F. Comparison between Comparative Example 3 and Example 1 shows that the initial bonding strength of Comparative Example 3 is better, but the CTE increases, and the resolution of the camera fails in the temperature shock test, resulting in blurred images, which cannot meet the requirements;
[0066] G. Comparison between Example 4 and Example 1 shows that different fillers are used. The filler in Example 4 has poor sphericity, poor stacking degree and poor compatibility with the surface treatment agent, which results in decreased strength. In addition, there are too many residual silanol groups on the surface of the powder, which makes the viscosity stability of the glue unable to meet the 20% change in 3 days.
[0067] H. Comparative Example 5 is compared with Example 1. The auxiliary agent I4 is used. I4 contains a low molecular weight unsaturated polycarboxylic acid polymer, which is different from the acid radical used in Example 1, and the acid value is too high, resulting in a slow reaction at 80°C, insufficient reaction, and low initial bonding strength. After reliability, further reaction increases the bonding strength, but curing causes increased shrinkage of the glue, and the camera resolution is NG.
[0068] In summary, it can be seen that the addition of the copolymer containing acidic polyester or the high molecular weight copolymer silyl ammonium salt of the present application can significantly improve the stability and viscosity of the glue, and enhance the stability of the product. It can be seen from the comparative examples that only by adding a specific content of auxiliary agent can a better and more stable effect be achieved. In order to achieve a better glue viscosity effect, the selection of resin is also critical. Experiments have shown that only by using a specific proportion of resin compounding in the present application can the overall toughening effect of the composition be achieved, thereby obtaining a better glue effect.
[0069] This embodiment also provides a camera assembly, which can be manufactured by bonding the components of the assembly using the epoxy adhesive composition of the above embodiments 1-4 to obtain a product with better stability.
[0070] The above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An epoxy adhesive composition, characterized in that: The composition comprises the following components in parts by weight: Epoxy resin 5-20 parts, toughening agent 2-10 parts, epoxy diluent 2-10 parts, light curing agent 0.1-1 parts, heat curing agent 0.1-1 parts, filler 40-80 parts, coupling agent 0.1-1 parts, thixotropic agent 5-10 parts, auxiliary agent 0.1-2 parts; The auxiliary agent includes one or more of a copolymer containing acidic polyester and a high molecular weight copolymer silane ammonium salt.
2. The epoxy adhesive composition according to claim 1, characterized in that: The acid value of the copolymer containing acidic polyester is in the range of 30 to 150 mg KOH / g; the amine value of the molecular weight copolymer silyl ammonium salt is in the range of 20 to 60 mg KOH / g.
3. The epoxy adhesive composition according to claim 1, characterized in that: The copolymer containing an acidic polyester includes a copolymer containing a phosphoric acid polyester.
4. The epoxy adhesive composition according to claim 1, characterized in that: The epoxy resin includes one or more of alicyclic epoxy resin and hydrogenated bisphenol A epoxy resin; the alicyclic epoxy resin includes one or more of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and bis((3,4-epoxycyclohexyl)methyl)adipate.
5. The epoxy adhesive composition according to claim 1, characterized in that: The toughening agent includes a core-shell toughening agent, and the core-shell toughening agent includes one or more of a mixture of core-shell styrene-butadiene rubber and epoxy resin, a mixture of core-shell butadiene rubber and epoxy resin, and a mixture of core-shell polybutadiene rubber and epoxy resin.
6. The epoxy adhesive composition according to claim 1, characterized in that: The epoxy diluent is an oxetane-type active diluent, and the oxetane-type active diluent includes one or more of 3-ethyl-3-oxetane methanol, 3,3'-(oxybismethylene)bis(3-ethyl)oxetane, and 4,4-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl.
7. The epoxy adhesive composition according to claim 1, characterized in that: The photocuring agent includes one or more of diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate and mixed triarylsulfonium hexafluorophosphate.
8. The epoxy adhesive composition according to claim 1, characterized in that: The thermal curing agent includes one or more of a thermal cationic polymerization initiator of a salt composed of a hexafluoroantimonate anion and a cation, and a thermal cationic polymerization initiator of a salt composed of a tetrakis(pentafluorophenyl)borate anion and a cation.
9. The epoxy adhesive composition according to claim 1, characterized in that: The invention comprises the following components in parts by mass: 3 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 3 parts of bis((3,4-epoxycyclohexyl)methyl)adipate, 3 parts of hydrogenated bisphenol A epoxy resin, 3 parts of core-shell structure toughener, 5 parts of 3-ethyl-3-oxetanemethanol, 1 part of diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, 1 part of thermal cationic polymerization initiator of a salt composed of tetrakis(pentafluorophenyl)borate anion and cation, 60 parts of silicon powder, 0.5 parts of glycidoxypropyltrimethoxysilane, 7 parts of fumed silica, and 0.1 parts of a copolymer containing phosphate polyester.
10. A camera assembly, characterized in that: The component is made by bonding the components of the assembly using the epoxy adhesive composition as described in any one of claims 1 to 9.